Cytotoxicity and Bioactivity of Calcium Silicate-based Cements in a Culture of Stem Cells from the Apical Papilla - Knorr, Adriana; Boldrin Mestieri, Leticia; Pinheiro , Lucas Siqueira; Mendes , Roberta Almeida; Gonzalez Hernandez, Pedro Antonio; Barletta , Fernando Branco; Grecca , Fabiana Soares (Iranian Endodontic Journal, 2021)
Introduction: The present in vitro study evaluated the cytotoxicity and bioactivity of commonly-used calcium silicate-based cements in a culture of stem cells from the apical papilla (SCAPs). Materials and Methods: NeoMTA Plus (Avalon Biomed), BiodentineTM (Septodont) and MTA HP Repair (Angelus) cements were evaluated using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) and sulphorhodamine-B (SRB) viability assays. Cells were seeded (1*104 cells mL-1) in 96-well plates and exposed to 1:4 diluted extract in 24 h and 72 h. For the analysis of bioactivity, alkaline phosphatase (ALP) enzyme activity and Alizarin Red S (AZR) were assessed after 24 h of cell culture in 12-well plates (1*104 cells mL-1), where cells were exposed to 1:4 diluted extract on days 1 and 7. Minimum Essential Eagle’s Medium alpha modification was used as control. ANOVA and Tukey’s post hoc test were used to compare the different cements at each experimental time point. Results: No significant differences were found between the cements and the control specimens on MTT at 24h and 72 h (P>0.05); however, the calcium silicate-based cement materials showed higher cell viability compared to the control group (P<0.05). In the 24-h SRB, NeoMTA Plus showed lower cell viability than BiodentineTM and MTA HP Repair (P<0.05), with all groups similar to the control group (P>0.05). Compared to 24-h results, only NeoMTA Plus presented increased cell viability at 72h (P<0.05). ALP activity was similar across the materials at 1day (P>0.05). ALP activity was higher for BiodentineTM when compared to NeoMTA Plus (P<0.05), nevertheless, it was similar to MTA HP Repair and control groups (P>0.05) at 7days. At 1- and 7-day periods ofAZR assay, BiodentineTM presented higher levels of mineralized nodule formation (P<0.05). Conclusion: All evaluated calcium silicate-based cements demonstrated cell viability and bioactivity, suggesting that these (bio)materials may be indicated for use in regenerative dentine-pulp complex procedures.